Records of brachyuran crabs (Decapoda) from seamounts in the Mariana Ridges, with description of a new species of Samadinia Ng & Richer de Forges, 2013, and rediscovery of Goniopugettia tanakae Sakai, 1986 - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2025)
A small collection of brachyuran crabs made during the KM20-10C cruise conducted by R/V Kaimei of JAMSTEC was studied. The specimens were collected using a suction sampler deployed on the KM-ROV (remotely operated vehicle); four species were identified. Two epialtid species were collected from Ritto Seamount in the West Mariana Ridge: Goniopugettia tanakae Sakai, 1986 at 666 m depth and Samadinia quindecimspina sp. nov. at 617 m depth, each represented by a single male specimen. Goniopugettia tanakae, previously known only from the female holotype of unknown locality, now has its male characteristics and distribution clarified through the present specimen. The generic diagnosis of Goniopugettia is updated. Samadinia quindecimspina sp. nov. appears close to S. griffini (Davie & Short, 1989) from Queensland, Australia, among the 38 known congeners, but is differentiated by its carapace gastric region armature, male pleon shape, and subtle first gonopod features. The remaining two species, Galilia petricola Komai & Tsuchida, 2014 (Leucosiidae) and Beuroisia major (Sakai, 1978) (Mathildellidae), were found at Nikko Seamount in the Central Mariana Ridge. The study also provides genetic data for the mitochondrial 16S rRNA and/or COI genes of these specimens.